Reciprocal relations between coach and athletes in female elite junior soccer: a shared reality perspective - Bjaaen, D. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Purpose: The context in talent development is complex where a collaboration between coach and athlete is necessary for optimal performance development. But it is cramped, where only a few athletes are identified as talents. Hence, it is important to have quality in the coach-athlete relationship, thereby making it more likely to have a shared reality about future development. Shared Reality Theory (SRT) contains: the motivation to connect with others and to create something meaningful. Indeed, SRT holds significant potential for studying the reciprocity in the coach-athlete relationship (Echterhoff & Higgins, 2018). Therefore, the purpose of the study is to investigate the reciprocity in the coach-athlete relationship and whether both parties share the same understanding of talent development. Design: Four female elite junior soccer players (Mage = 15.6 years) and their head coach were interviewed using a semi-structured interview (Mtime = 29.9 minutes). The players trained five days every week (Mduration = 1.5 hours) and played normally one match each week. Two out of four athletes play on the junior national team. Results: The coach is concerned with the players` individual needs, clear feedback, and building confidence. Verbal communication appeared to be an important finding among the coach`s attitudes, values, and goals in meeting with talent development. The athletes respond somewhat differently where findings indicate that the process of how to work toward their goals are unclear. Conclusion: According to SRT, there is a distance between what the various parties have of understanding in the process of developing future talents.